Cornukaempferia puangpeniae sp. nov. and C. aurantiiflora var. vespera var. nov. (Zingiberaceae) from Northern Thailand - Piyaporn Saensouk; Surapon Saensouk; Thawatphong Boonma; Chainarong Techa; Sarayut Rakarcha; Areerat Ragsasilp; Danh Duc Nguyen (Heliyon)
Thailand hosts a diverse array of plants in the Zingiberaceae family, with over 150 endemic species, highlighting its significance in global biodiversity. The genus Cornukaempferia stands out for its ornamental and medicinal value. During a research expedition in Northern Thailand, a previously unknown Cornukaempferia species was discovered in Sukhothai province, expanding the known distribution range. It was confirmed through comprehensive taxonomic analysis as a new species, Cornukaempferia puangpeniae. Additionally, a new variety, C. aurantiiflora var. vespera, was identified in Uttaradit Province. The genus now encompasses eight species and two varieties with the addition of these taxa, exhibiting a notable prevalence in Thailand and highlighting its significant endemism. Particularly, C. larsenii is noteworthy for being native to Thailand and Laos. Detailed morphological descriptions, including diagnoses with related taxa, were provided. The species' ecological characteristics, pollen morphology, traditional uses, and conservation status were documented. A revised key to species and varieties in the genus Cornukaempferia, including a UPGMA cluster analysis dendrogram elucidating morphological relationships within the genus, was presented. These discoveries contribute to the botanical knowledge of the region, underscoring the importance of continued exploration and conservation efforts in preserving its rich flora.